Dynamic Characteristics of Foot Development: A Narrative Synthesis of Plantar Pressure Data During Infancy and Childhood. Issue 4 (19th October 2021) - Montagnani, Eleonora; Price, Carina; Nester, Chris; Morrison, Stewart C.
Abstract : This narrative review aims to describe existing research reporting plantar pressure analysis in typically developing infants and children, to advance understanding of foot development. Abstract : Purpose: Quantifying plantar pressure throughout childhood enables clinicians to enhance knowledge of typical changes in foot function. This narrative review aims to describe existing research reporting plantar pressure analysis in infants and children developing typically, to advance understanding of foot development. Methods: A narrative approach was used; 263 articles were identified and 13 met inclusion criteria. Results: Plantar pressures during walking rapidly change in infancy and childhood. With development, pressures increasingly resemble those in adults with the development of initial heel contact, shift in pressure distribution from medial to lateral foot side, decreasing midfoot pressure magnitude. The literature has a variety of study designs, data collection protocols, and analysis. Conclusion: This review describes plantar pressure changes occurring as walking develops, emphasizing the typical trajectory of foot function development in infancy and childhood. The present finding describes the complex biomechanical development of foot function in typically developing infancy and childhood.